Intervention strategies against rotavirus in pigs - Meade, Nathan J. (2017)
The aim of this study was to investigate intervention strategies that have the potential to produce treatments reducing rotavirus-related disease in swine. Rotavirus is the biggest cause of viral gastroenteritis in young swine so is a huge economic burden to farmers. Cell lines deficient for innate anti-viral mechanisms were used to passage rotavirus. This novel vaccine strategy was investigated for its ability to elicit virus that is dependent on the modified cell lines for efficient replication and growth. Rotavirus isolates dependent on modified cell lines represent promising attenuated viral vaccine candidates. Whilst no rotavirus isolates were discovered with this characteristic, analysis of the viral genome after serial passage revealed non-synonymous single nucleotide polymorphisms causing non-conserved mutations at the protein level. Rotavirus isolates with these mutations may cause cell line dependency. A second intervention strategy used computer-assisted analysis (in silico) to reveal short potentially therapeutic peptides based on possible epitopes of rotavirus capsid proteins. Each synthetic peptide was not shown to block the rotavirus-host cell interaction in vitro. Peptides with this property could be used as candidate peptide-based anti-viral blocking drugs. In addition, peptides did not block the neutralising ability of anti-rotavirus antibodies found to be present in pig serum, which would then be used as immunogens to raise neutralising antibodies against rotavirus. However, inactivated rotavirus was found to bind serum antibodies in vitro and therefore appears to hold more promise as a therapeutic strategy than the synthetic peptides. Antibodies present in sow serum were discovered to cross-react with four different lab adapted strains of rotavirus. In contrast, antibodies directed against a common porcine genotype (G5P[7]) were not crossreactive against other strains. This study has initiated research into treatments against rotavirus-related disease in swine but potential vaccine and therapeutic candidates have not yet been revealed.